Measuring airway compliance of pulmonary fibrosis by endobronchial optical coherence elastography - Hang Xu; Jian-yi Niu; Zi-qing Zhou; Li-ya Lu; Chun-li Tang; Yang-huan Chen; Shi-yue Li; Ye Gu; Yu Chen (PLoS ONE, 2026)
Background Optical coherence elastography derived from optical coherence tomography for measuring soft tissue and organ compliance, holds promise in respirology but remains largely exploratory. Methods The airway lumen area (Ai) was measured by endobronchial optical coherence tomography in control subjects (n = 4), and pulmonary fibrosis (n = 8) while airway pressure (Paw) increased from 0–20 cm H 2 O. Airway compliance (AC) and airway specific compliance (ASC) were derived from the Paw vs. Ai curves. Evaluate correlations among Ai, AC, ASC, and lung function parameters. Results Endobronchial optical coherence elastography (EB-OCE) was constructed by ASC, which could detect AC and ASC among 3 rd to 7 th generations of bronchi. Pulmonary fibrosis tended to exhibit lower ASC in 5 th to 7 th generations of bronchi compared to controls. The ASC-7 appeared to be positively correlated with FEV₁, FVC, TLC, VC, and DLCO. Conclusions EB-OCE provides a novel approach to measure AC and extends the analysis to small airway. Pulmonary fibrosis appeared to show a heterogeneous reduction in AC across different bronchial generations compared to controls. A decline in ASC-7 was possibly associated with reduced lung function.